PERANCANGAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI ASRAMA MA’HAD ALY PUTRI MENGGUNAKAN TOGAF ADM - Nur Aida; Muftiyah Zakiyah; Akhlis Munazilin (CV. Denasya Smart Publisher, 2025)
This study aims to design an enterprise architecture for the Ma’had Aly Putri dormitory information system using the TOGAF ADM framework. The qualitative approach was employed to analyze business processes, data, applications, and technology architecture based on actual dormitory management conditions. The results of this study produce a comprehensive enterprise architecture design that integrates business processes, data entities, application modules, and supporting technology. This research highlights the novelty of applying TOGAF ADM in the context of Islamic boarding school dormitory management to support more structured, efficient, and integrated information systems.